Improving working readiness through mastering soft skills: Empirical evidence from university students in indonesia; Mejorar la preparación para el trabajo a través del dominio de las habilidades blandas: evidencia empírica de estudiantes universitarios en Indonesia - Kusni Ingsih; Suhana Suhana (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
The current study aims to examine and analyze the effect of soft skills on working readiness. Respondents of the current study were active students from several universities in Indonesia. The sampling technique used is non-probability sampling, namely convenient sampling. Data analysis were performed using multiple linear regression. The results show that learning throughout life skills, creativity, teamwork skills, and leadership skills significantly influence on working readiness. Meanwhile, problem-solving skills, communication skills, and ethics have no significant effect on working readiness. The results of the current study provide a theoretical contribution regarding the relationship between soft skills and working readiness. Future research is urgent to conduct to provide a clearer picture of the relationship between soft skills and working readiness. The current research gives students awareness to improve their soft skills. The study also provides a managerial contribution for universities to formulate the concept of developing soft skills for their students.
Keywords: I23; J24; J81; 330; soft skills; working readiness; university students